Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1016/s0022-5347(17)36059-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results with Vacuum Constriction Device

Abstract: From November 1985 to April 1990, 216 consecutive patients were treated with the vacuum constriction device. Patients were mailed an initial questionnaire (group 1) and a long-term questionnaire (group 2) at a median followup of 3 and 29 months, respectively. Of 202 available patients 161 in group 1 (75%) and 115 in group 2 (57%) responded. Regular use of the vacuum constriction device was reported by 69% group 1 and 70% group 2 patients. patient and partner satisfaction was 82% and 87% in group 1, and 84% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
12

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 11 publications
7
56
0
12
Order By: Relevance
“…The most common side effects include numbness, pain, penile bruising or petechiae. 9,32,37,[44][45][46] Due to the constriction rings, painful ejaculation or sensation of trapped ejaculate has also been commonly reported. 7,9 Other rare complications such as leg spasms, testicular migration, urethral varicosities/bleeding have been reported.…”
Section: Complicationsmentioning
confidence: 99%
“…The most common side effects include numbness, pain, penile bruising or petechiae. 9,32,37,[44][45][46] Due to the constriction rings, painful ejaculation or sensation of trapped ejaculate has also been commonly reported. 7,9 Other rare complications such as leg spasms, testicular migration, urethral varicosities/bleeding have been reported.…”
Section: Complicationsmentioning
confidence: 99%
“…7,8,10 In our early penile rehabilitation program, the VCD was the preferred erectile aid. The advantage of VCD is that the erections produced are independent of endogenous vasoactive substance such as nitric oxide (NO) production, which is impaired by nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Vacuum constriction devices (VCD) have been successfully used in a variety of patients with organic ED. 10 Its use included those patients treated for prostate carcinoma with either RP or radiation therapy. 7,8,10,11 Colombo et al 12 found that their patients who practiced early application of VCD without the constrictive band to produce 'stretching' for the smooth muscle fibers showed significant improvement of spontaneous erectile ability.…”
Section: Introductionmentioning
confidence: 99%
“…As with vacuum devices, they can be used only for a short period not exceeding 30 min, owing to the need for oxygenation of penile smooth muscle. 37 Second-line treatments. When first-line treatments fail or cannot be used, a more aggressive level of therapy is needed.…”
Section: Symptomatic Treatmentsmentioning
confidence: 99%